ENVIRONMENTAL TAXES AND THEIR IMPACT ON BUSINESS - Khalilova Nilufar Ahmatovna (Ecominds Press, 2025)
This article explores the essence of environmental taxes as a tool of environmental and economic policy. A comparative analysis of their implementation in various countries, including EU member states and developing economies, is presented. Special attention is given to the impact of environmental taxes on business: costs, motivation for green innovations, resource reallocation, and company competitiveness. The paper also examines the potential advantages and disadvantages of environmentally oriented taxation for the private sector and public fiscal policy. Conclusions are drawn about the need for a balanced approach in introducing environmental taxes.
Keywords: Environmental taxes, sustainable development, business, green innovations, fiscal policy, greening, tax burden, circular economy.